PENGARUH ENVIRONMENTAL MATURITY, FINANCIAL RISK, DAN GROWTH OPPORTUNITY TERHADAP FINANCIAL PERFORMANCE DAN FIRM VALUE - Eleonora Nathania Christi; Dwi Ratmono (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of environmental maturity, financial risk, and growth opportunity on firm performance and firm value in non-financial companies listed on the Indonesia Stock Exchange during the period 2021-2024. Firm performance as the first dependent variable is measured using Return on Assets (ROA), while firm value as the second dependent variable is measured using Price to Book Value (PBV). Environmental performance, firm size, leverage, and sales growth are the independent variables. Control variables, such as cash holdings, are included in this study to ensure a more comprehensive analysis. Data analysis is performed through multiple regression supported by descriptive statistical analysis and classical assumption tests.This study uses a quantitative approach by analysing secondary data from 65 non-financial companies, which were reduced to 24 companies after outliers were removed. The total non-financial company data used as a sample consisted of 260 observations before outliers and 96 observations after outliers over four years (2021-2024). The results of the study show a positive effect of growth opportunity on financial performance and firm value. Financial risk has a negative effect on financial performance and no effect on firm value. Meanwhile, environmental maturity has no effect on financial performance and firm value.